Absence of mycobacterial DNA in peripheral blood and artery specimens in patients with Takayasu arteritis. Issue 1 (January 2017) - Carvalho, Evanir; Souza, Alexandre; Leão, Sylvia; Levy-Neto, Maurício; Oliveira, Rosangela; Drake, Wonder; Franco, Marcello; Saldiva, Paulo; Gutierrez, Paulo; Andrade, Luís
Abstract The objective of this study was to demonstrate the presence of mycobacterial nucleic acid sequences in peripheral blood and arteries from patients with Takayasu arteritis (TA). Polymerase chain reaction was performed to detect mycobacterial DNA from three different nucleic acid sequences including the insertion sequence (IS)6110, the 65-kDa heat shock protein gene (HSP65 ), and the 16S ribosomal RNA (rRNA) gene in peripheral blood from 32 TA patients and in arterial specimens from 10 TA patients. Twenty-eight HIV-negative patients with pulmonary tuberculosis prior to therapy were tested for IS6110 in peripheral blood as positive controls, and 24 blood donors were evaluated as healthy controls (HC). All TA patients were negative for the insertion sequence IS6110 and forHSP65 and 16S rRNA genes in blood samples and in arterial specimens. IS6110 sequence was found in peripheral blood from 22 (78.5 %) patients with pulmonary tuberculosis but not in HC. In conclusion, the strategy of mycobacterial-specific nucleic acid amplification in the peripheral blood and arterial specimens of TA patients was unable to lend support to the association between TA and tuberculosis long suggested in the literature.